Contract Instructing within Aotearoa New Zealand’s Secondary Schools - Alan Haslip; Jo Straker; Sarah English (New Zealand Journal of Teachers' Work)
Over the last 150 years, outdoor education in Aotearoa New Zealand has evolved from teachers taking students out of school on field trips to running expeditions and adventure activities as part of the curriculum. Recent accidents have increased expectations within society for outdoor leaders including teachers to be technically skilled and qualified before taking groups outdoors. This has, prompted many schools to employ qualified contract instructors to deliver parts of their programme. Using a grounded theory approach, this research explores the complex relationships that exist between schools, teachers, and contract instructors. A model outlining different types of communication between schools and contractors highlights how many outdoor education outcomes remain undeclared and implicit. Recommendations are presented to help contractors and schools work together to deliver programmes which continue to achieve a broad range of outcomes